IMG-03. Impact of childhood cerebellar tumor surgery on cognition: Can fMRI serve as a surrogate marker?. (3rd June 2022) - Dorfer, Christian; Pletschko, Thomas; Seiger, Rene; Chocholous, Monika; Kasprian, Gregor; Roessler, Karl; Kollndorfer, Kathrin; Schöpf, Veronika; Leiss, Ulrike; Slavc, Irene; Prayer, Daniela; Lanzenberger, Rupert; et al.
Abstract: BACKGROUND: Childhood cerebellar pilocytic astrocytomas harbour excellent overall survival rates after surgical resection, but the patients may exhibit specific cognitive and behavioural problems emphasising our current understanding of the cerebellar role in cognition. Functional MRI has catalysed the mechanistic insights into brain functional systems and has already been linked with the neuropsychological performance. We aimed to exploit the question whether functional MRI can be used as a surrogate measure for the cognitive outcome assessment of these patients. METHODS: We investigated 13 patients (median age 22.0 years, range 15.2 – 31.7) after a median interval between surgery and examination of 15.0 years (range 4.2 – 20.8) and 16 matched controls. All subjects underwent a functional 3T MRI scans in a resting state condition and a battery neuropsychological tests. RESULTS: Patients showed a significantly increased functional connectivity in the precuneus compared to controls (p<0.05) and at the same time impairments in various domains of neuropsychological functioning such as a lower mean WIE IQ percentile (M = 48.62, SD = 29.14), lower scores in the TMT letter sequencing (M = 49.54, SD = 30.66), worse performance on the WIE subtest Digit Symbol Coding (M = 38.92, SD = 35.29), subtest Symbol Search (M = 40.75, SD = 35, 28), and TAP divided attention task (M = 783.92, SD = 73.20). CONCLUSION: Functional MRI has the potential to serve as a surrogate measure for the cognitive outcome assessment. The precuneus brain region is heavily involved in the cerebral associative oversight of cerebellar cognitive function.